Juvenile polyp in Thai children-clinical and colonoscopic presentation - Nuthapong Ukarapol (2018)
Background: The aim of this prospective study was to describe the clinical characteristics of colorectal polyp in Thai children. Methods: From December 2002 to February 2005, children under 15 years of age presenting with rectal bleeding were prospectively enrolled. Demographic, clinical, and laboratory information was recorded. Location, number, characteristics, and histopathology of the polyps were noted. Results: There were 32 patients with a mean age of 6.5 years. The most common presenting symptom was hematochezia, followed by prolapsing rectal mass and diarrhea. In 20 patients there was a single polyp, 6 had 2-4 polyps, and 6 were diagnosed with polyposis coli. Most of the polyps were located exclusively at the rectum and sigmoid colon. In only 7 cases were the polyps proximal to the rectosigmoid region. This included 6 patients who had polyps beyond the splenic flexure. All were juvenile polyps without evidence of adenomatous changes. Compared to those with isolated polyps, the patients with polyposis coli had a statistically significant incidence of right-sided polyps (P <0.001) and a history of prolapse of the rectal mass (P = 0.006). Conclusions: Because of the high prevalence of right-sided polyps and the concern about malignant transformation, colonoscopy should be considered as the initial evaluation in children with rectal bleeding. © 2007 Société Internationale de Chirurgie.